Assessment of knowledge in patients of surgical wards regarding clinical symptoms and diagnostics of most common malignant tumors - Kozłowska, Elżbieta; Szewczyk, Maria T. (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: The aim of this work was to evaluate the knowledge of symptoms and prophylaxis among hospitalized patients. Material and methods: The research was carried in the Provincial Hospital in Bydgoszcz (i.e. general surgery, gynecology and obstetrics, urology, breast surgery and thoracic surgery). 250 hospitalized patients took part in the tests, as well as 50 healthy people. The scientific method used was a specially designed questionnaire. The Bioethics Committee of Collegium Medicum of Mikołaj Kopernik University in Bydgoszcz approved these tests. Results : Patients from the Breast Diseases Ward had better knowledge about cancers than the control group. Symptoms of lung cancer were known to both groups to the same extent. Patients from the Clinical Ward of Thoracic Surgery were very knowledgeable about lung cancer, but they did not know anything about other malignant types of cancer. Patients from Gynecology and Obstetrics wards are better than the control group only at knowledge about symptoms and screening of cervix cancer. Patients from the Urology Ward have the best knowledge about screening of prostate cancer and colon cancer. Those hospitalized at the Surgery Ward do not know symptoms of colon cancer, but they have knowledge about its screening. Conclusions : 1. Patients from the Clinical Ward of Thoracic and Cancer Surgery and the Clinical Surgery Ward had the least knowledge about malignant tumors. 2. Patients from Urology, Gynecology and Obstetrics wards have better knowledge about malignant tumors treated there.